2020
DOI: 10.14569/ijacsa.2020.0110849
|View full text |Cite
|
Sign up to set email alerts
|

Movie Rating Prediction using Ensemble Learning Algorithms

Abstract: Over the last few decades, social media platforms have gained a lot of popularity. People of all ages, gender, and areas of life have their presence on at least one of the social platforms. The data that is generated on these platforms has been and is being used for better recommendations, marketing activities, forecasting, and predictions. Considering predictions, the movie industry worldwide produces a large number of movies per year. The success of these movies depends on various factors like budget, direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The author focused on the user's conformity in rating with a matrix-factorization-based conformity modeling technique. The result was a significant improvement compared to RMSE, so conformity modeling is important for movie rating studies [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The author focused on the user's conformity in rating with a matrix-factorization-based conformity modeling technique. The result was a significant improvement compared to RMSE, so conformity modeling is important for movie rating studies [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…By transforming the 1-10 rating result to only three categories--"Great", "OK", and "Poor", it gave a higher accuracy. (1) In a research to predict movie ratings before the movie is released, the author used data from IMDB including IMDB score, director, gross, budget and so on to train the mode. It concluded that Random forest gave the best prediction accuracy and number of voted users, number of critics for review, numbers of Facebook likes, duration of the movie and gross collection of movie affect the score most strongly [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian tersebut menggunakan metode kNN dan menghasilkan prediksi kesusksesan sebuah film dengan rating hits, netral dan gagal. Pada penelitian yang dilakukan oleh (Mhowwala, Sulthana dan Shetty, 2020) data dari IMDb, Youtube dan wikipedia diolah menggunakan algoritma random forest dan XGBoost untuk melakukan prediksi rating film. Dari penelitian tersebut didapat akurasi 95% pada XGBoost.…”
unclassified